A review of human carcinogens. Part F: chemical agents and related occupations (Lyon, 2012)
"This Volume 100F covers Chemical Agents and Related Occupations, specifically 4-Aminobiphenyl, Benzidine, Dyes Metabolized to Benzidine, 4,4'-Methylenebis(2-chloroaniline), 2-Naphthylamine, ortho-Toluidine, Auramine and Auramine Production, Magenta and Magenta Production, Benzo[a]pyrene, Coal Gasification, Occupational Exposures during Coal-tar Distillation, Coal-tar Pitch, Coke Production, Untreated or Mildly Treated Mineral Oils, Shale Oils, Soot, as found in Occupational Exposure of Chimney-sweeps, Occupational Exposures during Aluminium Production, Aflatoxins, Benzene, Bis(chloromethyl)ether and Chloromethyl Methyl Ether, 1,3-Butadiene, 2,3,7,8-Tetrachlorodibenzo-para-dioxin, 2,3,4,7,8-Pentachlorodibenzofuran, and 3,3',4,4',5-Pentachlorobiphenyl, Ethylene Oxide, Formaldehyde, Sulfur Mustard , Vinyl Chloride, Isopropyl Alcohol Manufacture by the Strong-acid Process, Mists from Strong Inorganic Acids, Occupational Exposures during Iron and Steel Founding, Occupational Exposure as a Painter, Occupational Exposures in the Rubber Manufacturing Industry. Because the scope of Volume 100 is so broad, its Monographs are focused on key information. Each Monograph presents a description of a carcinogenic agent and how people are exposed, critical overviews of the epidemiological studies and animal cancer bioassays, and a concise review of the agent's toxicokinetics, plausible mechanisms of carcinogenesis, and potentially susceptible populations, and life-stages. Details of the design and results of individual epidemiological studies and animal cancer bioassays are summarized in tables. Short tables that highlight key results are printed in Volume 100, and more extensive tables that include all studies appear on the Monographs programme website (http://monographs.iarc.fr). It is hoped that this volume, by compiling the knowledge accumulated through several decades of cancer research, will stimulate cancer prevention activities worldwide, and will be a valued resource for future research to identify other agents suspected of causing cancer in humans."